#RhodesMustFall: Using social media to "decolonise" learning spaces for South African higher education institutions: A cultural historical activity theory approach - Francis, S.; Hardman, J. (South African Journal of Higher Education, 2020)
Since the end of 2015, South African universities have been the stage of ongoing student protests that seek to shift the status quo of Higher Education Institutes through calls to decolonise the curriculum and enable free access to HEIs for all. One tool that students have increasingly turned to, to voice their opinions has been social media. In this article we argue that one can use Cultural Historical Activity Theory to understand how the activity systems of the traditional academy are shifting the wake of social media, with traditional power relations becoming more porous as students’ voices gain an audience. By tracing the historical development of CHAT, we show how 4th generation CHAT enables us to analyse potential power shifts in HEIs brought about through the use of social media.